Enhancing Students’ Computational Thinking Skills through Digital Ethnomathematics Learning with ECOPEDIA - Halimah Nur Agustin; Neni Mariana; Tatag Yuli Eko Siswono (Universitas Negeri Padang, 2026)
This study investigated the improvement of students’ computational thinking abilities through the implementation of digital ethnomathematics instruction supported by the ECOPEDIA platform. A quantitative methodology was adopted, employing a quasi-experimental pretest-posttest control group design. The research involved two class groups, namely an experimental cohort and a comparison cohort. The primary data collection tool was a computational thinking assessment, which had undergone validity and reliability testing prior to use. Based on the analysis, the experimental group’s mean score rose from 50.7 at pretest to 84.8 at posttest. The Independent Sample T-Test revealed a statistically meaningful difference between the two groups (p < 0.05). Furthermore, the experimental class achieved an N-Gain of 0.69, falling into the moderate category and surpassing that of the control class. In light of these results, the ECOPEDIA-based digital ethnomathematics approach proved to be more effective than conventional teaching methods in this particular sample (Cohen’s d = 0.82, indicating a large effect size). These outcomes suggest that culturally grounded digital media can serve as a promising instructional alternative for fostering 21st-century competencies, although further studies with broader sampling are recommended to confirm the generalizability of these findings